Dakwah Politik dalam Paradigma Simbiotik - Yakin, Syamsul (Jurnal Komunikasi Islam, 2019)
This paper examines the relationship between da’wah and politics based on a symbiotic paradigm. Through a historical-critical approach, this paper found that the relationship between da’wah and politics has an inseparable relationship. Historically, the Prophet Muhammad and the Muslim scholars have practised a symbiotic pattern of political da’wah. In this context, da’wah conducted within the frame of idealism, which is to spread the goodness of religious teachings. In this regard, various benefits and goodness for the community and get the pleasure of God. Furthermore, political propaganda emphasizes balance and benefit for the people. Therefore, propaganda and political symbiosis, at a certain level, have given room for the development of democracy. In this regard, it is necessary to have a proselytising management approach.